Massive hemorrhage from a unique old cesarean scar ectopic pregnancy with negative urine and serum β-HCG: a rare case report. Issue 8 (17th November 2018) - Yang, Xiao; Wei, Xiao-Qing; Feng, Dan; He, Wei; Chen, Yuan; Hua, Ping
ABSTRACT: Human chorionic gonadotropin (HCG) is an important indicator for the diagnosis of pregnancy. The authors report a unique case of cesarean scar ectopic pregnancy (CSEP) with negative urine and serum HCG levels, which was initially misdiagnosed as an intrauterine tumor despite the use of transvaginal ultrasound. Dilation and curettage was performed, which caused massive vaginal bleeding. Diagnostic hysteroscopy after uterine artery embolization and pathological examination of the surgical specimen confirmed the diagnosis of old CSEP. Postoperative follow-up showed that normal menstruation restarted 2 months later. This case reminds gynecologists and obstetricians the diagnosis of CSEP should be considered, especially when there is a mass at or near the surgical scar, regardless of the HCG level.